(untitled) (Journal of the College of Basic Education, 2022)
This research focused on studying the effect of insulating materials on the difference in the detailed climatic characteristics of two types of buildings in the city of Baghdad during one year, and the focus was on January, which represents the coldest month, and July, which represents the warmest month. The building, one of the two buildings consists of the ground floor and the first of cement, while the other consists of the ground floor of cement and the first floor consists of insulating material. The researcher concluded that the cement building has a higher temperature than the insulating building in summer, and that in the case of using air conditioning, the temperature will decrease in the insulating building by a degree more than the insulating building Cement, but in the winter, the insulating building needs